Invasive Group A Streptococcal Infections in Children: A Nationwide Survey in Finland. Issue 2 (February 2016) - Tapiainen, Terhi; Launonen, Saana; Renko, Marjo; Saxen, Harri; Salo, Eeva; Korppi, Matti; Kainulainen, Leena; Heiskanen-Kosma, Tarja; Lindholm, Laura; Vuopio, Jaana; Huotari, Tiina; Rusanen, Jarmo; et al.
Abstract : Background: The incidence of invasive group A streptococcus (iGAS) infections varies in time and geographically for unknown reasons. We performed a nationwide survey to assess the population-based incidence rates and outcomes of children with iGAS infections. Methods: We collected data on patients from hospital discharge registries and the electronic databases of microbiological laboratories in Finland for the period 1996– 2010. We then recorded the emm types or serotypes of the strains. The study physician visited all university clinics and collected the clinical data using the same data entry sheet. Results: We identified 151 children with iGAS infection. Varicella preceded iGAS infection in 20% of cases and fasciitis infection in 83% of cases. The annual incidence rate of iGAS infection was 0.93 per 100, 000 in 1996–2000, 1.80 in 2001–2005 and 2.50 in 2006–2010. The proportion of emm 1.0 or T1M1 strains peaked in 1996–2000 and again in 2006–2010, to 44% and 37% of all typed isolates. The main clinical diagnoses of the patients were severe soft-tissue infection (46%), sepsis (28%), empyema (10%), osteoarticular infection (9%) and primary peritonitis (5%). Severe pain was the most typical symptom for soft-tissue infections. More than half of the patients underwent surgery and received clindamycin. The readmission rate was 7%, and the case fatality rate was 2%. Conclusions: The incidence rate of pediatric iGAS infections tripled during our study. The increase was not, however, the result of a change in the strain types causing iGAS. Varicella immunization would likely have prevented a significant number of the cases.